Relations of Sex to Diagnosis and Outcomes in Acute Coronary Syndrome - Nils Arne Sörensen; Johannes Tobias Neumann; Francisco Ojeda; Sarina Schäfer; Christina Magnussen; Till Keller; Karl J. Lackner; Tanja Zeller; Mahir Karakas; Thomas Münzel; Stefan Blankenberg; Dirk Westermann; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
BackgroundThe atypical presentation of women with acute coronary syndrome (ACS) has been related to delayed diagnosis and treatment, which may explain worse outcome compared with men. Methods and ResultsWe analyzed pooled data of 2520 patients of 2 prospective cohorts in terms of differences in presentation and management of women and men suggestive of ACS. Using logistic regression, we established 2 diagnostic models and tested their diagnostic performance in both sexes separately. Sex‐specific differences in management of patients with ACS were ascertained and a 2‐year follow‐up was performed. Women were older than men (median 67 versus 61 years, P=0.001), had more often dyspnea (22% versus 18%, P=0.024), nausea or vomiting (26% versus 16%, P=0.001) and radiating chest pain (47% versus 40%, P=0.001). Classical risk factors (smoking, diabetes mellitus, dyslipidemia or known coronary artery disease) were less frequent in women. Diagnostic models showed no significant sex‐related differences in diagnostic performance in a “first contact” setting (medical history and symptoms) or after “complete triage” (including ECG and biomarkers). Women with ACS underwent coronary angiography (73.8% versus 84.3%, P<0.001) and revascularization (53.8% versus 70.1%, P<0.001) less frequently. Two‐year incidence of myocardial infarction and death was similar in both sexes, but revascularization and cardiac rehospitalization were more frequent in men. ConclusionsIn a large cohort of patients with suspected ACS, sex differences in clinical presentation did not impair diagnostic accuracy. Two‐year outcomes were comparable. Our findings suggest a benefit of chest pain units to minimize sex differences in ACS management and prognosis. Clinical Trial RegistrationURL: https://www.clinicaltrials.gov. Unique identifiers: NCT02355457 (BACC), NCT03227159 (stenoCardia).